Characterization of C-S Lyase from C. diphtheriae: A Possible Target for New Antimicrobial Drugs. (11th September 2013) - Astegno, Alessandra; Giorgetti, Alejandro; Allegrini, Alessandra; Cellini, Barbara; Dominici, Paola
Abstract : The emergence of antibiotic resistance in microbial pathogens requires the identification of new antibacterial drugs. The biosynthesis of methionine is an attractive target because of its central importance in cellular metabolism. Moreover, most of the steps in methionine biosynthesis pathway are absent in mammals, lowering the probability of unwanted side effects. Herein, detailed biochemical characterization of one enzyme required for methionine biosynthesis, a pyridoxal-5′-phosphate (PLP-) dependent C-S lyase from Corynebacterium diphtheriae, a pathogenic bacterium that causes diphtheria, has been performed. We overexpressed the protein in E. coli and analyzed substrate specificity, pH dependence of steady state kinetic parameters, and ligand-induced spectral transitions of the protein. Structural comparison of the enzyme with cystalysin from Treponema denticola indicates a similarity in overall folding. We used site-directed mutagenesis to highlight the importance of active site residues Tyr55, Tyr114, and Arg351, analyzing the effects of amino acid replacement on catalytic properties of enzyme. Better understanding of the active site of C. diphtheriae C-S lyase and the determinants of substrate and reaction specificity from this work will facilitate the design of novel inhibitors as antibacterial therapeutics.